Contenção com paredes de jet grouting em escavações cilíndricas: Análise dos efeitos do diâmetro da escavação - Gonçalo Guerra (2010)
Using a program based on the finite element method, a parametric study is performed toevaluate the effects of the excavation diameter on the behaviour of jet-grout walls in cylindricalexcavations. The program incorporates the Biot multidimensional consolidation theory (coupledformulation of the equilibrium and flow equations) with soil constitutive relations simulated bythe p-q- critical state model. Particular attention is given, during and after the constructionperiod, to the analysis of the excess pore pressure, stress levels and displacements in the ground,as well as of the stresses, displacements and earth pressures on the wall.